HUBUNGAN DURASI TIDUR DENGAN SIKLUS MENSTRUASI PADA MAHASISWI KEPERAWATAN UNIVERSITAS MUHAMMADIYAH SURABAYA - Supatmi Supatm; Ana Yusliana; Yuanita Wulandari; Fathiya LY (Sinar : Jurnal Kebidanan, 2019)
Objective: to find out the relationship between sleep and cycles of menstruation in college students at the Muhammadiyah University of Surabaya. Methods: This study used a correlation design with a cross-sectional approach. The population in this study was all nursing students in semester II, IV and VI in Muhammadiyah university of Surabaya as many as 213 academic year-old students 2019. Large numbers of 139 students in semester II, IV and VI careers were selected using the Cluster Random Sampling technique. Variables are dependent on sleep, menstrual dependencies. The data was analyzed using the ChiSquare test. Result: The results of the study showed most of the women who had less sleep (42.4%), and most experienced menstrual cycles in the literature (54%). This study showed the relationship between sleep deprivation and menstrual cycle with a value of Ï-value 0,000 <É‘ 0.05 which indicated that Ho was rejected. Short duration of sleep can be caused by serotonin synthesis or damage to the mucus of ramus. Conclusion: Therefore it affects the REM cycle which made the enthusiastic sleep. Serotonin levels decreased during lacteal phase. Therefore hormonal disruption results in loss of luteinizing hormone (LH) secretion and a decrease in estrogen levels which caused the menstrual cycle disorder.Â Keywords: Sleep Duration, Menstruation CycleÂ